Challenges and Opportunities in Implementing National Standards for English Teacher Professional Growth in Pontianak - Utin Ainun Kasmiri; Ghea Murtianda; Ririn Nurfajrini; Yohanes Gatot Sutapa Yuliana (English Department FBS UNP, 2026)
This classroom action research investigated the effectiveness of integrating the EXCUL (Explore, eXpress, Create, Use, Link) method as a pedagogical strategy to foster deep learning engagement among 11th-grade EFL students. Conducted over two intervention cycles, the study examined how experiential and culturally responsive learning sequences supported students’ participation, critical thinking, and meaningful language use. Data were collected through observations, student worksheets, learning artifacts, and engagement checklists, then analyzed using descriptive statistics and qualitative thematic coding.Findings showed a clear increase in students’ behavioral, emotional, and cognitive engagement after the implementation of EXCUL. Students became more active in collaborative tasks, demonstrated improved confidence in expressing ideas, and displayed stronger abilities to connect English learning with real-life cultural contexts. Quantitative scores of engagement and task performance also showed notable gains between Cycle 1 and Cycle 2. The study concludes that the EXCUL method effectively promotes deeper learning approaches by positioning students as active constructors of knowledge. These findings highlight the potential of experiential–cultural integration as a powerful model for student-centered English language teaching in Indonesian classrooms.